The Effect Of Online Learning On Student Creativity In Vocational High Schools - Fauziyah, Luluk Hamidah; Muhammad, Syuaiban; Azam Ismail, Raja (HAMKA INSIGHT, 2023)
This study aims to determine the effect of online learning on the creativity of class XI students of the Jakarta Vocational High School Accounting Expertise Program. The population in this study were 300 people and 35 people were taken as a sample. The research method used is associative quantitative research method. The sampling technique used was purposive sampling. Data was collected using a questionnaire/questionnaire. The results of this study indicate that there is an influence between online learning variables on student creativity variables of 51.4%. Thus it can be stated that online learning has a strong enough effect on student creativity. Therefore, the results of this study conclude that there is an effect of online learning on the creativity of class XI students in the accounting expertise program at SMK. This is also proven by (Siregar and Manurung, 2020) in his research which details "The Influence of Blended Learning on the Creativity of Prospective Teacher Students at Medan State University". Proving that based on testing the results of the posttest, it can be concluded that the blended learning strategy assisted by SIPDA Unimed has a significant effect on student creativity.